Case report: Double L611S/V617L JAK2 mutation in a patient with polycythemia vera originally diagnosed with essential thrombocythemia - Li, Xiao-qing; Liu, Jia-jun; Liu, Cheng-cheng (Frontiers in Oncology, 2022)
Double JAK2 mutations have rarely been described in myeloproliferative neoplasms (MPNs) and are demonstrated to be associated with the polycythemia vera (PV) phenotype. Here, we first report a case of a PV patient with a de novo double L611S/V617L in cis mutation of JAK2. A 40-year-old female was admitted to the hospital with massive splenomegaly, multiple splenic infarcts and abdominal pain. She had a 4-year history of erythrocytosis with an antecedent 10-year history of thrombocytosis before coming to our hospital. She was diagnosed with JAK2 L611S/V617L double-mutant PV after a detailed medical examination in 2017. According to the literature, IFNα therapy can induce clinical, hematological, histopathological, and occasionally molecular remission in individuals with MPNs. Our report demonstrates that combination therapy with ruxolitinib and IFNα can lead to a substantial reduction in JAK2 L611S/V617L double-mutant allele burden.